"Role of Sexual Risk Behaviors and Sexual Attitude in Perceived HIV Vulnerability Among Youths with Disabilities in Two Nigerian Cities" (2014)
"The role of sexual attitude and sexual risk-behavior in the perception of HIVvulnerability and differences among youths with disability and able-bodied youths was investigated. The cross-sectional survey included purposively selected youths with visual, hearing and physical impairments (n = 181) and able-bodied youths (n = 181 as comparison group) with mean age of 23.75 years in public institutions. Data was gathered with the use of a 44-item questionnaire which included a Braille version. Analysis included descriptive, cross-tabulation, and 2X2 ANOVA. Sexual risk behavior is related and has influence on perceived HIV-vulnerability in both groups, while sexual attitude did not. Youths with disability who have liberal sexual attitude and high score in sexual riskbehavior reported the highest perceived HIV-vulnerability. Visually-impaired participants perceived a higher level of HIV-vulnerability compared to the hearing and physically impaired. Health care planners should consider sexual risk behavior in improving perceived HIV-vulnerability in both impaired and able-bodied populations."